Health and safety management in a changing organisation: Case study global steel company. (April 2015) - Koivupalo, Maarit; Sulasalmi, Marko; Rodrigo, Philip; Väyrynen, Seppo
Graphical abstract: Highlights: Organisation creates challenges for HS management due to constant state of change. HS management practices and tools differ on local sites. HS management is based mostly on OHSAS 18001 in big global multi-site company. Improvements are needed to existing HS management practices and tools. HS can be managed based on well-defined corporate HS standards in similar situations. Abstract: When an organisation changes, grows, or new units join into a corporation, it generates challenges for health and safety (HS) management. There are different types of HS tools, systems, applications, forms and software which support HS management. The purpose of this research is to find out what kind of HS management practices and tools are used and what is required to manage HS efficiently within a global steel company's ( N employees = 15.000) different sites. All the sites ( N = 6) had a health and safety management system, which was based on OHSAS 18001 requirements. Local HS management practices and tools varied significantly, but had similar backgrounds. Corporate HS management was based around HS standards, vision and principles, plans and targets. Similarly, it also followed OHSAS requirements. Some improvement needs have been identified for both the local and the corporate level HS management practices and tools. It is possible to manage HS in a continuously changing organisation. The foundations should be based on corporate HS standards, which should be outlined clearly – based on the desired end result complying with the external requirements.